Colorectal lymph node harvest in cancer surgery, adequacy and treatment implication: a 5-year retrospective analysis from a tertiary hospital in Ethiopia - Jaleta, Sirna Emana; Abafogi, Abdo Kedir; Woyimo, Tamirat Godebo; Disassa, Gashahun Mekonnen; Usman, Sultan Jebel; Abagojam, Abduletif Haji-Ababor; Tukeni, Kedir Negesso (Frontiers in Gastroenterology, 2025)
IntroductionColorectal cancer is one of the common malignancies, and obtaining sufficient lymph nodes after surgeries is critical for staging and subsequent treatment planning. While guidelines advocate collecting at least 12 lymph nodes, insufficient lymph node sampling can have catastrophic consequences.MethodsThis was a retrospective study that looked at the parameters influencing lymph node retrieval during colorectal cancer surgery in one of tertiary hospital in Ethiopia. In this study, data from 85 patients’ records for stages I-III were analyzed and divided into two groups: adequately harvested and inadequately harvested. The association between potential factors impacting optimal harvests was analyzed.Results and discussionThe study found that the majority of cancer patients were between the ages of 34 and 53 years, in which the adequate lymph node retrieval was achieved only in 23% of cases. Procedures being performed by GI oncologic surgeons (P = 0.006, AOR;26.4), depth of invasion (AOR:14. P = 0.05), and length of specimen (AOR:5.365 P:0.045) were associated with improved adequacy of harvesting the lymph node. In conclusion, the study discovered that colorectal cancer primarily affects young people. Only a small number of participants had adequate lymph nodes harvested. The operating surgeon’s expertise, tumor characteristics, and specimen lengths were the most important elements influencing lymph node retrieval in colorectal cancer surgery in the setting. Adequate sample length, combined with better availability to more qualified operators, may improve the adequacy of harvest in guiding future treatment decisions.